The differences of food preferences, food choices and its waste with nutritional status among students receiving school supplementary meals in Kota Bharu, Kelantan - Tohar, Siti Hajar Mohd (Universiti Sains Malaysia, 2024)
Schools are an important food environment to cultivate and promote healthy food choices and practices among children and adolescents. This study aimed to identify the differences of food preferences and food choices and its waste with nutritional status among children students received school supplementary meals in Kota Bharu, Kelantan. Eligible schools were randomly selected from a complete list of public primary schools in Kota Bharu, Kelantan that was obtained from the Ministry of Education Malaysia's website. It involved a cross-sectional study that was conducted through a self-administered questionnaire among 130 school-aged children’ participants. The participants consisted of 38.5% (45) males and 61.5% (72) females. The participants will be selected based on the inclusion criteria, such as government-funded with non-religious and special educational needs, Malaysian citizens, primary school student’s male and female aged 7 to 12 years old, receive school supplementary meal program and able to understand Bahasa Malaysia. The questionnaire comprises three parts, Part One: Sociodemographic items, Part Two: Food Preferences which were classified based on food groups derived from Malaysian Food Pyramid and with the additional food groups in food preferences such as fast-food, processed foods, sugary foods and beverages and food items were chosen based on the most common foods found within school environment either from school canteen or brought from home to school, and Part Three: Food Choices that were provided within RMTs meals and its waste which refer from non- disliked meals within RMTs. The findings challenge the common perception that overweight and obese individuals have higher consumption rates of unhealthy foods. On the contrary, this study revealed that underweight individuals consume fried foods more than those who are overweight or obese. Gender differences in food preferences were evident, with girls showing more diverse and healthier food choices compared to boys, though no differences were found in unhealthy food preferences across BMI categories. Additionally, the study highlighted food waste behaviours, showing that underweight students waste less food compared to their normal and overweight/obese peers.